2018
DOI: 10.3389/fchem.2018.00517
|View full text |Cite
|
Sign up to set email alerts
|

Li2O-Reinforced Solid Electrolyte Interphase on Three-Dimensional Sponges for Dendrite-Free Lithium Deposition

Abstract: Lithium (Li) metal, with ultra-high theoretical capacity and low electrochemical potential, is the ultimate anode for next-generation Li metal batteries. However, the undesirable Li dendrite growth usually results in severe safety hazards and low Coulombic efficiency. In this work, we design a three-dimensional CuO@Cu submicron wire sponge current collector with high mechanical strength SEI layer dominated by Li2O during electrochemical reaction process. The 3D CuO@Cu current collector realizes an enhanced CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It has been reported that the localcurrent density can be reduced by using high-surface-area current collectors [38][39][40][41][42][43][44][45][46][47], which results in a significantly improved cycling performance. Hence, only a uniform and strong artificial SEI, instead of native SEI, can alter the fundamental self-amplifying behavior of dendritic growth [2,26,[48][49][50][51][52][53][54][55][56][57][58][59]. Recently, several research groups aimed to artificially develop a stable SEI to protect Li anode [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the localcurrent density can be reduced by using high-surface-area current collectors [38][39][40][41][42][43][44][45][46][47], which results in a significantly improved cycling performance. Hence, only a uniform and strong artificial SEI, instead of native SEI, can alter the fundamental self-amplifying behavior of dendritic growth [2,26,[48][49][50][51][52][53][54][55][56][57][58][59]. Recently, several research groups aimed to artificially develop a stable SEI to protect Li anode [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, only a uniform and strong artificial SEI, instead of native SEI, can alter the fundamental self-amplifying behavior of dendritic growth [2,26,[48][49][50][51][52][53][54][55][56][57][58][59]. Recently, several research groups aimed to artificially develop a stable SEI to protect Li anode [48][49][50][51][52][53]. For instance, Huang's group [60] has prepared an artificial soft-rigid protective layer for dendrite-free Li anodes.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, high-energy-density storage batteries are urgently needed to satisfy the increasing demand in electric vehicles, consumer electronics and grid energy storage (Manthiram et al, 2017; Fan et al, 2018). Lithium metal secondary batteries have been considered as the potential candidate for high-energy-density storage batteries, since lithium metal anode possessed the highest theoretical specific capacity (3,862 mAh g −1 ) and the lowest reduction potential (−3.04V VS. standard hydrogen electrode) (Shen et al, 2018; Wu et al, 2018). Moreover, lithium metal used as the anode can even act as the lithium source in the battery with non-lithiated materials such as sulfur or oxygen as the cathode to achieve higher storage capacity compared to the current commercial lithium-ion batteries (Pan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In order to further develop the practical use of lithium metal as anode, scientists made great efforts to solve the lithium dendrites problems and achieved much progress on suppressing dendrite formation and growth (Li D. et al, 2018; Nie et al, 2018; Shen et al, 2018; Wu et al, 2018; Pan et al, 2019). Strategies such as electrolyte modification, multifunctional barriers, composite metallic lithium electrode, and 3D current collectors were proposed to suppress the formation of Lithium dendrites (Wu et al, 2018; Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Li metal is the most promising anode material for the next-generation batteries (Li-metal batteries), such as Li-S batteries (Su et al, 2018) and Li-air batteries (Cao et al, 2019), due to the lowest electrode potential (−3.04 V, compare to the hydrogen electrode) and the high capacity (3,860 mAh g −1 , which is 10 times than the commercial graphite) (Liu et al, 2016; Yan K. et al, 2016; Liang et al, 2017; Zhang K. et al, 2017; Bai et al, 2018; Cheng et al, 2018, 2019; Li et al, 2018; Terlicka et al, 2019). However, the intense chemical activity of Li metal leads to sever interface reactions between Li and electrolyte, which results in low Coulomb efficiency and increasing interface impedance (Zheng et al, 2014; Shen et al, 2018). Besides, the inhomogeneous Li deposition leads to forming the dangerous Li dendrites on the Li anode (Tao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%